If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7/x+5=5/6x-4
We move all terms to the left:
7/x+5-(5/6x-4)=0
Domain of the equation: x!=0
x∈R
Domain of the equation: 6x-4)!=0We get rid of parentheses
x∈R
7/x-5/6x+4+5=0
We calculate fractions
42x/6x^2+(-5x)/6x^2+4+5=0
We add all the numbers together, and all the variables
42x/6x^2+(-5x)/6x^2+9=0
We multiply all the terms by the denominator
42x+(-5x)+9*6x^2=0
Wy multiply elements
54x^2+42x+(-5x)=0
We get rid of parentheses
54x^2+42x-5x=0
We add all the numbers together, and all the variables
54x^2+37x=0
a = 54; b = 37; c = 0;
Δ = b2-4ac
Δ = 372-4·54·0
Δ = 1369
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1369}=37$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(37)-37}{2*54}=\frac{-74}{108} =-37/54 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(37)+37}{2*54}=\frac{0}{108} =0 $
| 5(x-1)+2(x+3)=0 | | 3(x+6)+2(x+3)=0 | | -x+5=-2x+6 | | 6t-3=12 | | 6x+8.06=3x+14 | | 8a+12=6a+14 | | -2(x-5)^2=36 | | -x+3=3x+9 | | -2/5w=6 | | 4x^2=-160 | | 3y^2-y=1 | | (4,5)m=-4/5 | | 15X-27=4x-6 | | 3x+7=-8+2x | | 5^2x+4=1/25^x+2 | | 6x−(7x−12)=101 | | 4z/10+3=-6 | | 15x-3(x-5)=3-15x+3 | | 5(3x-2)=9x+2 | | 1/x=2.22 | | 11x+15=3x-7 | | -1=w/8+4 | | x+4=10021 | | 3/5x+1/4=7/4 | | .6x+.25=1.75 | | 69=4w-11 | | -22=4x-2 | | x÷3+(2x+4)=2x÷15-6x+7÷30 | | p-27=836 | | 257=q-694 | | 5x+3÷(2)-7-4x÷(5)=-x-6÷(3) | | 11j=616 |